2009
DOI: 10.1002/eji.200939307
|View full text |Cite
|
Sign up to set email alerts
|

Education of hyporesponsive NK cells by cytokines

Abstract: NK-cell tolerance to self is mediated via engagement of inhibitory receptors by cognate MHC molecules. This event is critical for NK-cell education to achieve functional competence. Thus, NK cells expressing self-MHC-specific inhibitory receptors are responsive to activating stimuli while those lacking such receptors are hyporesponsive. Nevertheless, the mechanisms underlying NK-cell education are still poorly understood. Here, we show that after stimulation with cytokines, hyporesponsive NK cells acquire stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…It has been previously shown that CD56 dim KIR Ϫ (hyporesponsive) NK cells can up-regulate KIR after cytokine stimulation 14,23 and that only those cells that de novo express self MHC-specific KIR are licensed to kill. 29 Percentage of KIR up-regulation on proliferating cells is comparable between KIR Ϫ CD62L ϩ and KIR Ϫ CD62L Ϫ NK cells (supplemental Figure 2E). However, due to their extensive proliferation, a consistently higher proportion of KIR ϩ cells were generated from CD56 dim CD62L ϩ compared with CD62L Ϫ NK cells, suggesting that cells endowed with strong proliferative ability might have a higher chance to be licensed.…”
mentioning
confidence: 89%
“…It has been previously shown that CD56 dim KIR Ϫ (hyporesponsive) NK cells can up-regulate KIR after cytokine stimulation 14,23 and that only those cells that de novo express self MHC-specific KIR are licensed to kill. 29 Percentage of KIR up-regulation on proliferating cells is comparable between KIR Ϫ CD62L ϩ and KIR Ϫ CD62L Ϫ NK cells (supplemental Figure 2E). However, due to their extensive proliferation, a consistently higher proportion of KIR ϩ cells were generated from CD56 dim CD62L ϩ compared with CD62L Ϫ NK cells, suggesting that cells endowed with strong proliferative ability might have a higher chance to be licensed.…”
mentioning
confidence: 89%
“…CD56 dim NK cells can be separated on the basis of KIR/NKG2A expression into four consecutive maturation stages. 15 MDS patients had an unusually high frequency of NKG2A -KIR -CD56 dim NK cells ( Figure 6A). This subset represents an immature differentiation stage that is functionally not educated and is generally hyporesponsive to various stimuli.…”
Section: Phenotypic Analyses Revealed Immature Differentiation State mentioning
confidence: 99%
“…Uneducated KIR 2 NKG2A 2 NK cells are present in human peripheral blood and have been found to be hyporesponsive to various stimuli while displaying a mature phenotype (9)(10)(11). The phenotypic stability of hyporesponsive NK cells may, however, be debated as cytokine stimulation can induce uneducated KIR 2 NKG2A 2 NK cells to acquire effector functions and expression of KIR and/or NKG2A (9,12). In addition, uneducated NK cells have been found to be equally functional as educated NK cells in secretion of IFN-g during Listeria monocytogenes infection and are the primary mediators in suppression of mouse CMV infection (13,14).…”
mentioning
confidence: 99%